KOMPETENSI PEDAGOGIK GURU DALAM MENGEMBANGKAN KEMAMPUAN KREATIVITAS MATEMATIKA PESERTA DIDIK PADA PEMBELAJARAN JARAK JAUH - Irene Kristina Telaumbanua; Kurnia Putri Sepdikasari Dirgantoro (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2022)
Mathematics lessons are taught to equip students to have various thinking abilities. One of the most important thinking skills in mathematics is the ability to think creatively or it is called creativity. In fact, the creativity abilities of grade VII students at a Christian school in Toraja are still lacking in terms of indicators of mathematical creativity. One of the competencies that must be possessed by a teacher to be able to encourage the development of mathematical creativity of students is pedagogical competence. Therefore, the purpose this paper is to explain the implementation of teacher pedagogical competences during online learning to develop students' mathematical creativity. The research results describe the problems of mathematical creativity found in schools and how the implementation of teacher pedagogical competence as a solution to develop students' mathematical creativity. This qualitative research used observation method to collect the data of two classes with forty students as the population and twenty students are taken as the sample. The conclusion is that pedagogical competence can help the development of students' mathematical creativity, but the development has not occurred evenly because there are obstacles during online learning. So, Christian teachers still need to make efforts so that students can develop creative abilities as a means of knowing God more deeply. Suggestions given are that Christian teachers continue to apply interactive methods on an ongoing basis, deepen their insights into problem solving materials and problems, and try other approaches that consider other mathematical abilities such as mathematical reasoning or connections.